Strengthening civil society organizations:: models review toward an evaluation proposal - Gutiérrez-Diez, María del Carmen; Reyes López, José Gerardo; Alvarado Yañez, Jorge Arturo; Sapién Aguilar, Alma Lilia; Piñón Howlet, Laura Cristina (Archives of Business Research, 2019)
The relevance of Civil Society Organizations (CSO) is growing. Due to this, it is pertinent to look for strategies that strengthen them. This work seeks to compare five different theoretical models associated with the strength, institutional capacities, and maturity of CSOs, which allows the integration of a system for evaluating them. Through a documentary and bibliographic analysis, with a descriptive scope, the components and concepts of strength and maturity of each of the models studied are described and contrasted. The results allows to establish the fundamentals for the conceptualization of an evaluation system based on these concepts.